When do strategic alliances inhibit innovation by firms? Evidence from patent pools in the global optical disc industry - Joshi, Amol M.; Nerkar, Atul (Strategic Management Journal, 2011)
Abstract Research and development (R&D) consortia are specialized strategic alliances that shape the direction and scope of firm innovation activities. Little research exists on the performance consequences of participating in R&D consortia. We study the effect of patent pools, a unique form of R&D consortia, on firm performance in innovation. While prior research on alliances generally implies that patent pools enhance firm innovation, our study finds the opposite. Analyzing data on systemic innovation in the global optical disc industry, we find that patent pool formation substantially and significantly decreases both the quantity and quality of patents subsequently generated by licensors and licensees relative to the patenting activity of nonparticipants. Our empirical findings suggest that patent pools actually inhibit, rather than enhance, systemic innovation by participating firms. Copyright © 2011 John Wiley & Sons, Ltd.